Manufacturing blood ex vivo: a futuristic approach to deal with the supply and safety concerns - Singh, Vimal K.; Saini, Abhishek; Tsuji, Kohichiro; Sharma, P. B.; Chandra, Ramesh (Frontiers in Cell and Developmental Biology, 2014)
Blood transfusions are routinely done in every medical regimen and a world wide established collection, processing/storage centers provide their services for the same. There have been extreme global demands for both raising the current collections and supply of safe/adequate blood due to increasingly demanding population. Since, various risks remain associated with the donor derived blood, and a number of post collection blood screening and processing methods put extreme constraints on supply system especially in the underdeveloped countries. A logistic approach to manufacture erythrocytes ex-vivo by using modern tissue culture techniques have surfaced in past few years. There are several reports showing possibilities of RBCs (and even platelets/ neutrophils) expansion under tightly regulated conditions. In fact, ex vivo synthesis of few units of clinical grade RBCs from a single dose of starting material such as umbilical cord blood has been well established. Similarly, many different sources are also being explored for the same purpose such as embryonic stem cells, induced pluripotent stem cells. However, the major concerns remain elusive before the manufacture and clinical use of different blood components may be used to successfully replace the present system of donor derived blood transfusion. Most important factor shall include the large scale of RBCs production from each donation unit within a limited time period and cost of their production both of these issues need to be handled carefully since many of the recipients among developing countries are unable to pay even for the freely available donor derived blood. Anyways, keeping these issue in mind, present article shall be focused on the feasibilities of blood production and their use in near future.